PENGARUH SUMBER AIR MINUM DAN SANITASI LINGKUNGAN TERHADAP KEJADIAN GIZI KURANG PADA BALITA DI KABUPATEN KUPANG - Kadek Dwi Ariesthi; Odilia Esem; Hironima Niyati Fitri (Universitas Citra Bangsa, 2020)
The high rate of malnutrition in NTT is still a tough job that must be handled by the government. The many factors that influence the incidence of malnutrition require cross-sector cooperation to solve this malnutrition problem. One of the indirect causes of malnutrition is environmental sanitation. This study aims to determine the effect of drinking water sources and environmental sanitation on the incidence of malnutrition among children under five in Kupang Regency. This type of research is a descriptive study with a case control design. This research was conducted from July to August 2020 in Noelbaki Village, Kupang Regency, which consisted of 114 toddlers as samples and mothers as respondents. Data were collected by conducting direct interviews at each respondent's house. Data analysis was carried out by bivariate to determine the direction of the relationship between the independent variable and the dependent variable. Based on the results of the study, it was found that unprotected drinking water sources had a 9 times greater risk of causing undernutrition in children under five and environmental sanitation that was less at 5 times greater risk of causing under nutrition.